Точність визначення параметрів двох динамічних мікрооб'єктів за допомогою телевізійного сканувального оптичного мікроскопа - Шклярський, В. І.; Матієшин, Ю. М.; Баланюк, Ю. В.; Гудзь, Б. В. (Видавництво Львівської політехніки, 2013)
At the present stage of technological development there are more problems associated with micro- and nanotechnology. Among such problems occupy an important place task analysis of dynamic processes and several dynamic microobjects (MO) parameters simultaneously in view of the microscope in different fields (medicine, microbiology, ecology, microelectronics etc.). Identification number of dynamic parameters (for example, mobility) of some living cells and their components occurs mainly by using optical microscopy methods. To determine the mobility is most often used in two ways: 1) the method of fluorescence microphotographs analysis; 2) the method of quantitative fluorescence confocal laser scanning microscopy. Using these methods were quantitatively and qualitatively describes the process of intracellular transport, particularly cytoplasm-nuclear, kinetic accumulation in the nucleus of cells of different types of proteins, localization of drugs aimed at developing ways to intracellular delivery of anticancer drugs. To solve these and many such important tasks in the fields of medicine and microbiology can be successfully used television scanning optical microscope (TSOM) based on cathode ray tubes ultrahigh resolution, as provided in this scan resolution up to 0.1 ... 0.2 micron. This article contains analysis of the capabilities of this microscope in the case of the simultaneous study of several MO, which are move randomly - with variable speed and direction of motion. The basic principles of TSOM work in determining the dynamic parameters of separate MO and averaged parameters of several MO are submitted. Track each individual MO occurs by the use of scan mode of miniraster, the center of which the current frame is formed with coordinates that correspond to coordinates of the center of the MO in the previous frame scan. Interval of definition of coordinate position of each MO in sight of TSOM corresponds to the duration of one frame scanning at a constant speed scanning. Dimensions of the scanning raster should be reduced to the values 1...10% of the full-scale raster, while receiving miniraster. However, a scan should be used for MO of proportionate size with minimal scanning spot that move randomly at high speed. Among the MO for which the use of the scanning mode is not appropriate, you can select one or several MO simultaneously with large size (5...40 % of the full-scale raster in the plane of study). For such MO should be used only scanning with a full-scale square raster. Based on these considerations, we construct a mathematical model of the scanning process and analyze the significance of dynamic parameters which can be determined by TSOM using scan mode with a full-scale raster and tracking eachMO by miniraster. Розглядаються питання використання телевізійного сканувального оптичного мікроскопа для визначення різних параметрів динамічних мікрооб’єктів, які перебувають у групі, із застосуванням режимів сканування повноформатним растром та слідкування за кожним окремим мікрооб’єктом за допомогою сканувального мінірастра. Наведені принципи роботи мікроскопа, що забезпечують визначення параметрів як окремих динамічних мікрооб’єктів, так і групи загалом.
Accuracy of determination of two dynamic microobjects parameters with television scanning optical microscope
Keywords: television scanning optical microscopy; parameters of microobjects group; scanning miniraster; телевізійна сканувальна оптична мікроскопія; параметри групи динамічних мікрооб’єктів; сканувальний мінірастр